A Case Study Application Of Linear Programming And Simulation To Mine Planning ? Synopsis - J. A. de Carvalho Junior (The Southern African Institute of Mining and Metallurgy, 2012)
This paper analyses the impact of the uncertainty associated with the input parameters in a mine planning optimization model. A real example was considered to aid in the building of a mathematical model that represents the coal production process with reference to the mining, processing, and marketing of coal. This model was optimized using the linear programming concept whereby the best solution was perturbed by the stochastic behaviuor of one of the main parameters involved in the production process. The analysis of the results obtained permitted an evaluation of the risk associated with the best solution due to the uncertainty in the input parameters.